2008
DOI: 10.1002/dvdy.21561
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of BMP3 during chick limb development

Abstract: Bone morphogenetic proteins (BMPs) play diverse roles in many aspects of skeletal development and bone homeostasis. During endochondral ossification, tight regulation of BMP activity is required to assure proper survival, proliferation and differentiation of skeletal progenitor cells into chondrocytes and osteoblasts. BMP3, a structurally divergent member of the BMP family, acts as a negative regulator of bone formation by limiting BMP signal transduction. In this study, we focus on the chick limb where we fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…It is likely that the perichondrium negatively regulates chondrocyte maturation through more than one mechanism and this may include BMP3 controlling signaling through ActRIIB. The phenotype we observed in the BMP3 transgenic mice is similar to that seen in BMP3 infected chick limbs where expanded zones of hypertrophic chondrocytes and altered perichondrial formation also occur (Gamer et al, 2008). Taken together, these data suggest that the periosteum and the perichondrium and its adjacent chondrocytes are important targets for BMP3 action.…”
Section: Discussionsupporting
confidence: 72%
“…It is likely that the perichondrium negatively regulates chondrocyte maturation through more than one mechanism and this may include BMP3 controlling signaling through ActRIIB. The phenotype we observed in the BMP3 transgenic mice is similar to that seen in BMP3 infected chick limbs where expanded zones of hypertrophic chondrocytes and altered perichondrial formation also occur (Gamer et al, 2008). Taken together, these data suggest that the periosteum and the perichondrium and its adjacent chondrocytes are important targets for BMP3 action.…”
Section: Discussionsupporting
confidence: 72%
“…The BMP-3 molecule demonstrates high affinity to the activin receptor ActRII, but lower to ActRIIb. Next, the signal is carried to the cell nucleus using the SMAD protein [27]. Expression is located mainly in the neuroectodermis and the forming s periosteum, which suggests that BMP-3 may be engaged in www.journals.viamedica.pl [25], own modified.…”
Section: The Bmp Protein and Bmpr Receptor: Expression Function And mentioning
confidence: 99%
“…Among the local signaling pathways that are known to play a role in these processes are the canonical Wnt signaling (Akiyama et al, 2004; Hartmann, 2006; Hartmann and Tabin, 2000; Hu et al, 2005; Kawakami et al, 2000; Kawakami et al, 1999; Krishnan et al, 2006; Westendorf et al, 2004; Yamaguchi et al, 1999), bone morphogenetic protein (BMP) (Canalis et al, 2003; Ducy and Karsenty, 2000; Hoffmann and Gross, 2001; Kronenberg, 2003), parathyroid hormone related peptide (PTHrP), Indian Hedgehog (Ihh) (Chung et al, 1998; Chung et al, 2001; Karaplis et al, 1994; Karp et al, 2000; Kobayashi et al, 2002; Kronenberg, 2003; Lanske et al, 1999; Schipani et al, 1997; St-Jacques et al, 1999; Vortkamp et al, 1996) and fibroblast growth factor (FGF) (Colvin et al, 1996; Kronenberg, 2003; Marie, 2003; Ornitz, 2005; Wang et al, 1999) pathways. Several studies have demonstrated that the perichondrium regulates cartilage growth, by providing a source of signaling molecules that regulate chondrocyte proliferation and differentiation (Di Nino et al, 2001; Gamer et al, 2008; Hinoi et al, 2006; Long and Linsenmayer, 1998; Marie, 2003; Ornitz, 2005; Vortkamp et al, 1996). …”
Section: Introductionmentioning
confidence: 99%